Sodium-ion storage properties of nickel sulfide hollow nanospheres/reduced graphene oxide composite powders prepared by a spray drying process and the nanoscale Kirkendall effect. Issue 40 (24th September 2015) - Park, G. D.; Cho, J. S.; Kang, Y. C.
Abstract : Spray-drying and the nanoscale Kirkendall diffusion process are used to prepare nickel sulfide hollow nanospheres/reduced graphene oxide (rGO) composite powders with excellent Na-ion storage properties. Abstract : Spray-drying and the nanoscale Kirkendall diffusion process are used to prepare nickel sulfide hollow nanospheres/reduced graphene oxide (rGO) composite powders with excellent Na-ion storage properties. Metallic Ni nanopowder-decorated rGO powders, formed as intermediate products, are transformed into composite powders of nickel sulfide hollow nanospheres/rGO with mixed crystal structures of Ni3 S2 and Ni9 S8 phases by the sulfidation process under H2 S gas. Nickel sulfide/rGO composite powders with the main crystal structure of Ni3 S2 are also prepared as comparison samples by the direct sulfidation of nickel acetate–graphene oxide (GO) composite powders obtained by spray-drying. In electrochemical properties, the discharge capacities at the 150 th cycle of the nickel sulfide/rGO composite powders prepared by sulfidation of the Ni/rGO composite and nickel acetate/GO composite powders at a current density of 0.3 A g −1 are 449 and 363 mA h g −1, respectively; their capacity retentions, calculated from the tenth cycle, are 100 and 87%. The nickel sulfide hollow nanospheres/rGO composite powders possess structural stability over repeated Na-ion insertion and extraction processes, and also show excellent rate performance for Na-ion storage.